Explaining Changing Trends in Political Participation in Britain between 1983 and 2015 - KERNAGHAN, MATTHEW (2018)
The way in which citizens choose to express themselves in the political realm has changed dramatically in recent decades and clear trends have developed whereby voter turnout, party membership and other forms of institutionalised political engagement are caught in a downward spiral compared to innovative ways of civic engagement appearing to be on the rise across most liberal democracies (Dalton, 2008; Inglehart & Catterberg, 2002; Klingeman & Fuchs, 1995; Norris, 2002; Pattie et al., 2004).This thesis will therefore use the three theories of Social Capital, Cognitive Mobility and General Incentives in an attempt to assess the causes of, and ultimately explain, these aforementioned trends. The three theories each take a very different approach and will therefore offer a broad spectrum of potential explanations